Molecular Changes in Vapor‐Based Polymer Thin Films Assessed by Characterization of Swelling Properties of Amine‐Functionalized Poly‐p‐xylylene. Issue 19 (13th September 2020) - Koenig, Meike; Trouillet, Vanessa; Welle, Alexander; Hinrichs, Karsten; Lahann, Joerg
Abstract: Though widely applied in various technological areas, the knowledge about the molecular behavior of poly‐ p ‐xylylene and its derivatives prepared via chemical vapor deposition polymerization is still far from comprehensive, as for this polymer the characterization is limited due to the insolubility in most common solvents. This report presents the investigation of the swelling properties of aminomethyl‐functionalized poly‐ p ‐xylylene as a means to elucidate the influence of various process parameters on the structural properties of the polymer layer. The swelling of films with varying thickness, storage time and conditions, thermal treatment and deposited by varying the temperature of the deposition stage is measured. To gain deeper insight into the origin of the observed effects, the swelling measurements by spectroscopic ellipsometry are complemented using additional characterization methods. Abstract : The swelling properties of amine‐functionalized poly‐ p ‐xylylene films are investigated in order to probe changes in the molecular structure. As most representatives of this class of polymers are insoluble in common solvents, usual polymer characterization is limited. The effect of various process parameters on the swelling ability is tested and discussed.